1979
DOI: 10.1002/mus.880020208
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of alcoholic neuropathy: Morphologic, electrophysiologic, and biochemical findings

Abstract: A chronic high alcohol intake was induced in rats through the use of two procedures: the schedule-induced polydipsia technique and the liquid diet technique. Rats consumed 11-12 g of ethanol per kilogram body weight per day for 16 to 18 weeks. Morphologic evidence of a mild distal axonal neuropathy in the ventral caudal nerve was proposed. The red blood cell transketolase levels were normal, indicating that the rats were not deficient in thiamine and suggesting that the axonal degeneration was due to the direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 43 publications
2
34
1
Order By: Relevance
“…Rats chronically fed ethanol exhibited mechanical and thermal hyperalgesia and tactile allodynia, all of which are symptoms frequently occurring in patients with painful peripheral neuropathy (Scadding, 1992). This model is highly relevant to painful alcoholic neuropathy in humans because the blood alcohol level that results in neuropathic changes is similar (Bosch et al, 1979;. Also, the fact that hyperalgesia is stable for weeks renders this model very useful for study of underlying mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…Rats chronically fed ethanol exhibited mechanical and thermal hyperalgesia and tactile allodynia, all of which are symptoms frequently occurring in patients with painful peripheral neuropathy (Scadding, 1992). This model is highly relevant to painful alcoholic neuropathy in humans because the blood alcohol level that results in neuropathic changes is similar (Bosch et al, 1979;. Also, the fact that hyperalgesia is stable for weeks renders this model very useful for study of underlying mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to thiamine deficiency, recent studies indicate a direct neurotoxic effect of ethanol or its metabolites. Axonal degeneration has been documented in rats receiving ethanol while maintaining normal thiamine status [30]. Human studies have also suggested a direct toxic effect, since a dose-dependent relationship has been observed between severity of neuropathy and total lifetime dose of ethanol [29,31].…”
Section: Pathogenesismentioning
confidence: 98%
“…Although neuropathy is frequently seen in chronic alcoholics, there have been few reports on its prevalence (9-50%) (Bolton, 1987;Charness et al, 1989;Victor, 1994;Monforte et al, 1995;Pessione et al, 1995). Alcohol-related neuropathy is also associated with several risk factors, such as malnutrition, thiamine deficiency, direct toxicity of alcohol and a family history of alcoholism (Victor, 1975;Bosch et al, 1979;Claus et al, 1985;Monforte et al, 1995;Pessione et al, 1995), but it is not clear which of these plays a primary role in inducing neuropathy (Estruch et al, 1993;Palliyath and Schwartz, 1993). While the hyperalgesia produced by neuropathy has been demonstrated in animal models of other neuropathic pain states, there are few animal models of alcoholic neuropathy.…”
Section: Introductionmentioning
confidence: 99%